PENGARUH PASTA ZnO HASIL SINTESIS DENGAN PENAMBAHAN POLI VINIL ALKOHOL (PVA) DAN DISH DETERGENT TERHADAP EFISIENSI DYE-SENSITIZED SOLAR CELL (DSSC) DARI EKSTRAK BUNGA ROSELA(Hibiscus sabdariffa L.) - Pratiwi, Rr. Dian; ,M.Si, Drs. Gunawan; ,M.Si, Khabibi (Chem Info Journal, 2013)
A study the effects of synthesized ZnO pasta with the addition of poly vinyl alcohol (PVA) and dish detergent on the efficiency of dye-sensitized solar cell (DSSC) of rosella flower extract (Hibiscus sabdariffa L.) had been done. The purpose of this study was to obtain ZnO from the precursor of Zn(CH3COO)2.2H2O with precipitation method as a semiconductor material in DSSC prototype and to determine the influence of synthesized ZnO pasta with poly vinyl alcohol and dish detergent to the dye-sensitized solar cell. The method used in this study with the manufacture of ZnO was by precipitation method using precursor of Zn(CH3COO)2.2H2O. The results obtained were analyzed by XRD, FTIR spectrophotometry, and SEM. ZnO crystals obtained had a size of 25.676 nm and pore size of 71.43 nm. ZnO was then used as a semiconductor in DSSC using dye rosella extract. ZnO pasta was added with variation of binders that attached to the FTO glass using PVA and dish detergent. The efficiencies obtained from each variation was 0.225x10-3% for PVA while 0.138 x10-3% for dish detergent. PVA binder can produce better efficiency of DSSC.